Comparison of atlantoaxial and lumbosacral cerebrospinal fluid centesis techniques in South American camelids - Ester Malmström; Robert C. Cole; Erik H. Hofmeister; Jere K. Stern; Thomas Passler (Journal of Veterinary Internal Medicine, 2024)
Abstract Background Iatrogenic blood contamination during cerebrospinal fluid (CSF) centesis is common, which can limit the diagnostic usefulness of the sample. A novel ultrasound‐guided CSF collection technique is described in horses, by which CSF is obtained from the atlantoaxial (AA) space. Hypothesis/Objectives To compare ultrasound‐guided AA centesis with lumbosacral (LS) centesis in South American camelids (SAC). The hypotheses were that AA centesis would yield samples with less blood contamination although being technically more challenging than LS centesis. Animals Eight clinically healthy adult SAC from a university‐owned teaching herd. Methods Single‐blinded, randomized, 4‐way, 4‐period crossover study in which 2 veterinarians each performed both centesis techniques on each animal once. Cytological sample analysis was performed, and the technical difficulty of sample acquisition was assessed. Results The CSF was collected successfully and without complications by either technique during all collection attempts. Aspects of technical difficulty and concentrations of CSF analytes did not vary significantly between techniques. Median total nucleated cell and red blood cell counts were 1/μL and 0.5/μL and 167.5/μL and 155/μL for AA and LS techniques, respectively. The median total protein concentration was 32.9 mg/dL and 38 mg/dL for AA and LS centeses. A median of 1 attempt was necessary for both centesis techniques and the median number of needle repositioning events was 1 for AA and 0 for LS. Conclusion and Clinical Importance Depending on clinical circumstances, ultrasound‐guided AA centesis appears to be an acceptable alternative to other techniques for collection of CSF from SAC.